Mobility Boundaries Between Home, Community, and Beyond: Experiences of Exceptionally Old Adults Living in Eastern Canada - Gouliquer, Lynne; Poulin, Carmen; Lesmana, Maryani (Qualitative Sociology Review, 2015)
Mobility for older people is linked to various meaningful and celebrated ways of ageing, such as maintaining independence, community participation, and quality of life (Metz 2000). In this paper, we examine the lives of people aged 90 and over as they encounter mobility challenges in the face of a particularly neoliberal socio-economic political context. Fifteen Canadians, living independently, were interviewed using the Psycho-Social Ethnography of the Commonplace (P-SEC) methodology. They shared their experiences with managing physical and community-related mobility issues. The analysis reveals how the current public transportation system complicates the lives of the exceptionally old, and sheds light on the ways in which this population makes sense of and deals with these complications. With the goals of reducing social boundaries and enhancing community mobility of older adults, based on the findings, we offer social policy recommendations.